CONSTRUCTION OF THE FOREST SCHOOL FRAMEWORK BASED ON INDIGENOUS KNOWLEDGE IN MALAYSIA - Norwaliza Abdul Wahab; Pauline Swee-Choo Goh; Eng-Tek Ong; Mohd Hairy Ibrahim; Haryanti Mohd Affandi (LPMPP Universitas Negeri Yogyakarta, 2020)
The rate of drop outs among indigenous or Orang Asli pupils in primary school is a worrying issue. They were found to be unable to apply the knowledge acquired through formal education systems in Malaysia due to the different 'setting' of the environment. This failure was due to the lack of understanding on how Orang Asli pupils learn, think, and act. The aim of this study was to construct a Forest School framework for the teaching and learning process in Orang Asli primary schools. The qualitative study design involved in-depth interviews with six experts from the Orang Asli community by using semi-structured questions to explore and clarify related sub-constructs. The results showed five elements that need to be incorporated in the syllabus were: indigenous music, herbs and medicine, handicrafts, tools for hunting and forestry. The Forest School framework would serve as a comprehensive guide and reference for policymakers as indigenous knowledge elements need to be incorporated in primary school's syllabus to ensure life sustainability of Orang Asli in the forest. Teachers could take advantage to help Orang Asli pupils to feel more enthusiastic and motivated in processing the knowledge given in classrooms as it hits close to their environment.